2007
DOI: 10.1016/j.joca.2007.02.021
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy, safety and carry-over effect of diacerein in the treatment of painful knee osteoarthritis: a randomised, double-blind, NSAID-controlled study

Abstract: Diacerein was as effective as piroxicam in reducing pain and improving function but, unlike piroxicam, displayed a carry-over effect and a better safety profile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
76
1
6

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(85 citation statements)
references
References 24 publications
2
76
1
6
Order By: Relevance
“…In NSAID-controlled studies, although the NSAID had an earlier onset of efficacy, the effect with diacerein was similar after 1 month, with a better safety profile (34). Therefore, given current concerns about the safety of NSAIDs and COX-2 inhibitors, diacerein could be safely used instead of these drugs in the treatment of OA, especially in elderly patients who cannot take NSAIDs and COX-2 inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…In NSAID-controlled studies, although the NSAID had an earlier onset of efficacy, the effect with diacerein was similar after 1 month, with a better safety profile (34). Therefore, given current concerns about the safety of NSAIDs and COX-2 inhibitors, diacerein could be safely used instead of these drugs in the treatment of OA, especially in elderly patients who cannot take NSAIDs and COX-2 inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…Human studies have found diacerein to be effective for treating OA [13,17,26] . In 2007, Louthrenoo and colleagues [26] reported on the efficacy, safety and carry-over effect of diacerein, in comparison to piroxicam, in the treatment of Thai patients with symptomatic knee osteoarthritis.…”
Section: Discussionmentioning
confidence: 99%
“…In 2007, Louthrenoo and colleagues [26] reported on the efficacy, safety and carry-over effect of diacerein, in comparison to piroxicam, in the treatment of Thai patients with symptomatic knee osteoarthritis. Ninety percent of the patients treated with diacerein showed significantly reduced pain compared with 70% baseline.…”
Section: Discussionmentioning
confidence: 99%
“…The American College of Cardiology Foundation (ACCF)/American College of Gastroenterology (ACG)/ American Heart Association (AHA) 2008 expert consensus recommends discontinuing treatment with of NSAIDs in patients with gastrointestinal events, such as gastrointestinal bleeding (3). However, discontinuing NSAID and/or LDA therapy impairs the quality of life and increases the risk of thrombosis (4).…”
Section: Introductionmentioning
confidence: 99%